2007
DOI: 10.1253/circj.71.1845
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Evaluation of Atorvastatin in Patients With Coronary Heart Disease A Serial Intravascular Ultrasound Study

Abstract: oronary heart disease (CHD) is the leading cause of death in developed countries, and hypercholesterolemia is an independent risk factor for the progression of atheromatous plaque. Elevated serum cholesterol is causally associated with increased risk of CHD, and a series of randomized trials [1][2][3][4][5][6] have confirmed the benefits of HMG-CoA reductase inhibitors (statins) for hypercholesterolemia in the primary and secondary prevention of CHD. A recent meta-analysis showed that statin therapy reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
0
20
1
Order By: Relevance
“…Therefore, statins should be prescribed for Chinese CHD patients, besides their benefit of lipid lowering. [26][27][28][29][30] In this study, 82.2% of the participants received statin therapy, which was higher than a result from Japan (36.3%) 31 and from Hong Kong where a report showed that only 37% of participants received lipid-lowering drugs. 32 It is also higher than the results of small trials in China and other reports.…”
Section: Discussioncontrasting
confidence: 75%
“…Therefore, statins should be prescribed for Chinese CHD patients, besides their benefit of lipid lowering. [26][27][28][29][30] In this study, 82.2% of the participants received statin therapy, which was higher than a result from Japan (36.3%) 31 and from Hong Kong where a report showed that only 37% of participants received lipid-lowering drugs. 32 It is also higher than the results of small trials in China and other reports.…”
Section: Discussioncontrasting
confidence: 75%
“…It is well known that low-density lipoprotein cholesterol (LDL-C) is a strong risk indicator for CVD, and the reduction of serum LDL-C levels with statins (3-hydroxy-3-methyl-glutaryl CoA reductase inhibitors) is a well-established treatment to reduce the CVD risks. The clinical usefulness of IVUS has been clearly proven by showing not only the regression in plaque volume but also the change of its composition during statin therapy [9][10][11] . Therefore, the reduction of serum LDL-C levels achieved by statins improves the clinical outcomes and modifies the histology of the plaque in the coronary arteries; however, many patients with well-controlled LDL-C levels achieved by statins still continue to experience cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57][58] Because of the comprehensive information provided by carotid MRI, this technique is also ideal for monitoring vessel wall changes under treatment. Carotid MRI has been extensively validated for its ability to monitor plaque regression.…”
Section: Clinical Study Of Carotid Mri Of Atherosclerosis Carotid Lesmentioning
confidence: 99%